Striking Features of the Labor Market - William H. Greene; Ana P. Martins (Economics and Econometrics Research Institute (EERI), 2002)
The present paper develops a simple asymmetrical informational model that allows us to understand the individuals willingness to participate in a strike. We develop and compare two signaling models of strikes: in one, firms are able to monitor and enforce hours and offer different workweeks to the two types of workers a previous part-time/full-time wage schedules separating equilibrium was presented. In the other, only one work-week schedule can be offered.
Keywords: J52; J41; D82; C24; C25; 330; Strikes; asymmetric information; signaling; labor contracts; part-time work; mean or grouped data and limited dependent variables; binary choice models with mean or grouped data; sample selection with mean data